DECONSTRUCTING DAVID PELZER'S IDENTITY IN THE NOVEL A CHILD CALLED 'IT' - Sri Ariyani Lestari, - (2007)
This research is entitled "Deconstructing David Pelzer's Identity in the Novel A Child Called 'It'. It takes the issue of identity of the main character in David Pelzer's A Child Called 'It' as its main concerns. A descriptive method was used in analyzing the data and answering the main research question: What is the deconstructed identity of David Pelzer in the novel A Child Called 'It'? To conduct the research, the textual analysis was employed and the data of analysis are presented in tables and in narratives. The subject of analysis was the main character of the novel entitled A Child Called 'It'. The analysis, then, was conducted using Derrida's theory of deconstruction. The analysis had shown that the main character's identity was described as "playing" between the identity of master and slave, insider and outsider, centered and decentered, and subject and object. It was evidenced that his identity seemed to be changing and intertwined between the two opposing identities. This paper is expected to have a significant contribution to those who concern in conducting researches about the issue of identity.